Gemcitabine and carboplatin treatment in patients with relapsing ovarian cancer - Sufliarsky, J; Chovanec, J; Svetlovska, D; Minarik, T; Packan, T; Kroslakova, D; Lalabova, R; Helpianska, L; Horvathova, D; Sevcik, L; Spacek, J; Laluha, A; et al. (Neoplasma, 2009)
Despite progress in primary treatment of patients with advanced ovarian cancer, the majority develop recurrence of the disease. A platinum salt treatment, either as monotherapy or in combination with another cytostatic agent, is indicated for patients who have relapsed 6 or more months after primary treatment and thus have platinum-sensitive relapse. Because repeated use of paclitaxel treatment may lead to substantial neurotoxicity, the combination of gemcitabine with carboplatin represents a suitable treatment option, which is widely used in common clinical practice in the Czech Republic and Slovakia. This non-interventional, prospective study observed the effectiveness and tolerability of second-line treatment with gemcitabine and carboplatin in patients with platinum-sensitive relapse of ovarian cancer in routine clinical practice. The primary endpoint was to evaluate the survival and secondary endpoints were to evaluate time to disease progression, objective tumor response rate, and treatment toxicity. Patients were enrolled to planned second-line treatment with gemcitabine and carboplatin (gemcitabine 1000 mg/m2 and carboplatin AUC 5 on Day 1, and gemcitabine 1000 mg/m2 on Day 8 of a 21-day cycle) for platinum-sensitive relapse of ovarian cancer as a part of routine clinical practice and followed for 12 months. The events (death, tumor progression), tumor response, and maximal grades of toxicity were recorded according to common clinical practice. Survival time (using Kaplan-Meier analysis) and objective tumor response rate were calculated using data forms, and a subgroup analysis was performed using log rank tests for time-to-event endpoints; p-values were also calculated. Response rates were calculated for the whole population; for the subgroups, the Fisher's exact test was performed and only p-values were calculated. Between January 2004 and June 2005, 53 patients were enrolled in the study. The median age was 57 years and 96% of patients had an Eastern Cooperative Oncology Group Performance Status (ECOG-PS) of 0 and 1 at baseline. Approximately 91% of patients were originally diagnosed with stage III or IV; 60% of patients had disease free intervals (DFIs) of 12 or more months from previous therapy, and the additional 40% less than 12 months. The 1-year survival rate was 83%. Median survival time was not determined within the 12-month period following the start of the treatment study due to the limited duration of follow-up. Objective tumour response rate was 67.3%. Most common reasons for discontinuation of therapy were "Planned treatment completed" (53%) and "Tumor progression" (11%). Most common toxicities were leukopenia, anaemia, neutropenia, and thrombocytopenia; grades 3 and 4 of these toxicity types did not exceed 30%. Febrile neutropenia was recorded in two patients. Most common non-haematological toxicities were nausea and vomiting, fatigue, and neuropathy; grades 3 and 4 of these were below 6%. Results on time to disease progression are not published due to inconsistent statistical analysis of reported data. Based on this observation from routine clinical practice, which corresponds with previously published results from controlled clinical trials, the gemcitabine and carboplatin combination seems to be a suitable therapeutic option for patients with platinum-sensitive relapse of ovarian cancer.
Keywords: senioři; Immunoenzyme Techniques; Carboplatin; Disease Progression; senioři nad 80 let; Gemcitabine; Carcinoma, Endometrioid; progrese nemoci; mucinózní adenokarcinom; Prognosis; serózní cystadenokarcinom; výsledek terapie; Deoxycytidine; Middle Aged; Neoplasm Recurrence, Local; míra přežití; nádory vaječníků; mladý dospělý; Adult; lokální recidiva nádoru; nádory endometria; Prospective Studies; Endometrial Neoplasms; karboplatina; Aged, 80 and over; Neoplasm Staging; imunoenzymatické techniky; Young Adult; ženské pohlaví; prognóza; endometroidní karcinom; prospektivní studie; Adenocarcinoma, Mucinous; deoxycytidin; Humans; Survival Rate; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; gemcitabin; staging nádorů; Cystadenocarcinoma, Serous; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; Ovarian Neoplasms; Treatment Outcome; lidé